SDBE-MOG: Secure Dynamic Bits Encryption for Multi Owner Group Data Sharing in Cloud - Easwaramoorthy, Sathishkumar; Subburaman, Dhivya; S, Deepanjali. (International Journal of Engineering and Technology, 2018)
Cloud computing is considered as the cost-efficient and practical resolution for group data sharing within the cloud group members. Unluckily, distributing data in a multi- owner way and defending data with unique privacy in cloud is a challenging issue because of the repeated change or deletion of the members. The proposed multi-owner group management system uses novel scheme GCAURDL-FBS( Group Creation, Add Member, Revocation, Deletion, Login with Forward & Backward Secrecy) to control overall group management. GCAURDL-FBS using SDBAES (Secure Dynamic Bits Advance Encryption Standard) secures the group data sharing. The major objectives of this research is 1) data security, 2) data integrity, 3) data sharing without using secret key re-computation / re-encryption, 4) forward and backward secrecy, 5) proper group owner / member revocation and 6) avoiding collusion attack, brute force attack and Structured Query Language Injection attack. Any member in group can confidently impart their information through entrusted server. Owner / Member revocation is achieved by a novel scheme; it is not necessary to compute/alter the secret keys of other members. The proposed scheme supports data integrity and efficient group member/owner revocation. Ultimately, it is found that, proposed scheme is also secure, scalable and efficient in relative to the relevant schemes. This is revealed in the security and tentative analysis
Keywords: SDBAES; Group Signature; Data Integrity; Data Sharing; Forward & Backward Secrecy; Group Owner / Member Revocation.